IDENTIFIKASI MODEL PEMANFAATAN DAN PENGELOLAAN KAWASAN HUTAN (STUDI KASUS PERHUTANAN SOSIAL DI PULAU-PULAU KECIL) - Tidore, Faedly H.; B, Sabaruddin; Kurniawan, Andy; Tamrin, Mahdi (Prodi Kehutanan Universitas Khairun, 2025)
Abstarct The impact of various forestry policies on land management and conflict resolution in North Maluku, Indonesia. This research highlights significant regulatory measures and their impact on social forestry schemes, such as Village Forests, Customary Forests, and Community Forests. The study in Moya Village, Ternate, reveals challenges in forest management and utilization, emphasizing issues such as land use conflicts and inadequate support for local communities. As well as the issues social forestry institutions and related agencies in the area face. This study underscores the need for effective conflict resolution strategies and increased field support to minimize disputes. There are strategic steps that must be taken to minimize both vertical and horizontal conflicts. This study uses a qualitative descriptive method, focusing on stakeholders involved in forest management, and employs snowball sampling. This study shows that while social forestry policies facilitate legal access to forest management, their implementation often lacks adequate direction and support, leading to conflicts and inefficiencies. Two landowners privately manage the utilization and management of the forest area in Taman Moya. Regulations had previously been issued regarding establishing the forest area as a social forestry scheme. The management and utilization of the area became private due to internal conflicts within KUPS Cahaya Gamalama Keywords: Land Management, land use conflict, forest management